Epidural Catheter Tip Cultures: Results of a 4-Year Audit and Implications for Clinical Practice. Issue 4 (1st July 2000) - Simpson, R. S.; Macintyre, P. E.; Shaw, D.; Norton, A.; McCann, J. R.; Tham, E. J.
Abstract : Background and Objectives: The aims of this study were to evaluate the clinical relevance of routine microbiological culture of epidural catheter tips after use in acute pain management, and to identify patterns of culture result with respect to both indications for, and duration of, epidural catheterization. Methods: The Acute Pain Service (APS) reviews all patients under its care at least daily and keeps detailed records on each. Over a 4-year period, when APS protocol required epidural catheter tips to be sent for microbiological culture on removal, the APS saw 1, 810 patients who had received epidural analgesia. The records of these patients were reviewed. Results: Culture results were available for 1, 443 (79.7%) patients: 1, 027 catheter tips (71.2%) were sterile, while 416 (28.8%) were positive for at least 1 type of microorganism. Clinically, no epidural space infections were identified. The highest positive culture rates were found from epidural catheters used in the treatment of pain from fractured ribs or fractured pelves, while the lowest incidences occurred in elective orthopedic and thoracic surgery. The proportion of epidural catheters with positive culture results steadily increased with the duration of catheterization, but there were no clinically significant differences for catheters left in situ for either 3 or 4 days. Conclusions: We concluded that a significant proportion of epidural catheter tips may be "culture positive" after removal. It is suggested that this probably represents colonization of the skin at the catheter insertion site and subsequent contamination of the catheter tip on removal of the catheter. The large number of "culture positive" tips in the absence of clinically identifiable epidural space infection suggests that routine culture of epidural catheter tips is clinically irrelevant in the vast majority of cases, and that it is not a good predictor of the presence of an epidural space infection.